Comparison of intraocular pressure variability detected by day diurnal variation to that evoked by water drinking - Kadambi, Sujatha V (Indian J Ophthalmol, 2021)
PURPOSE: To determine correlation and agreement between intraocular pressure (IOP) peak and fluctuations detected by day diurnal variation (day DVT) to that after the water-drinking test (WDT). METHODS: Patients (18–80 years) with glaucoma, suspects, and ocular hypertension (OHT) were enrolled. IOP readings were taken on applanation tonometer, at 2-h intervals, from 8 AM to 3 PM (DVT). 3 PM IOP served as WDT baseline. Patients consumed water (10 mL/kg) in 5–15 min, at 3 PM, after they fluid fasted for 2 h. IOP was recorded every 15 min, from 3.30 to 4.30 PM. RESULTS: A total of 200 eyes (100 patients) were included. 58.5% were established glaucoma, 32% suspects, 9.5% OHT. Correlation between mean and peak IOP by WDT and day DVT was strong and significant (r = 0.89, P < 0.00; r = 0.73, P < 0.00) while it was weak for fluctuation (r = 0.12, P < 0.07). Agreement on Bland and Altman plots was limited for mean IOP and poor for peak and fluctuations. CONCLUSION: An exaggerated WDT response may indicate a compromised outflow facility and warrant close patient monitoring but the WDT cannot substitute day DVT in our clinical practice.